Pre-planned Vs. Executed Real-Time Pacing Strategies during 3-km Race: Role of Rating Perceived Exertion. Issue 3 (2nd July 2020) - Alves, Danilo L.; Cruz, Ramon; Bara, Crystina L. B. P.; Osiecki, Raul; Lima, Jorge R. P.; De-Oliveira, Fernando R.
ABSTRACT: Purpose : The aim of the study was to verify the agreement between preplanned and executed pacing during a 3-km race and determine whether adjustments are mediated by the rating of perceived exertion (RPE). Method : Thirteen young runners (eight males and five females, 17.5 ± 2.1 and 17.0 ± 1.6 years old, respectively) with national and international experience participated in the study. Before the simulated competition, the athletes informed of their preplanned pacing for the distance through a dashboard with the most common pacing profiles and were also asked to complete a questionnaire communicating their preplanned RPE for each lap of race. During 3-km, heart rate (HR), executed RPE and lap time were recorded. Results : Our results showed no significant association between preplanned and executed pacing ( p = .631). Moreover, no significant difference between preplanned and executed RPE was found, including the analysis by laps and phases. RPE and HR increased over time during the race ( p < .001). Conclusions : The athletes changed from their preplanned pacing, however, their RPE were similar in the preplanned and executed during the 3-km race. These findings indicate that the RPE could be responsible for adjustments in the pacing strategy.